(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This paper discusses the relationship between health, hygiene, and productivity of an employee in the workspace of manufacturing and a service industry. Health and Hygiene can be both physical and mental. Though European and American addresses the significance of health differently, Europeans tend to focus on the employer and the latter on the employee. In general, the trend of workspace health promotion in any sector is relatively small. Many specific tools and programs used in Occupational health and safety of the manufacturing sector and in Integrated psychological wellbeing of the service sector. The analysis of the above program suggests existing tools are insufficient to address the progressive challenges.